PSXIV-15 The Effect Of Intravaginal Progesterone Implant In The Vaginal Microbiota Of Holstein Cows. (7th December 2018) - Zanella, E; Zanella, G; Quadros, D; Bondan, C; da Silva, A; Faccioli, F; Lof, L; Cantão, M; Zanella, R
Abstract: Characterization of the vaginal microbiota in the livestock animals is of great interest to improve reproductive performance. With the objective of better comprehension of the possible causes of reproductive failure affecting cattle during the synchronization, we have characterized the vaginal microbiota of Holstein cows. The use of intravaginal implants with progesterone is a common procedure used to synchronize cows. It is known that these implants can cause vaginitis possibly altering the normal vaginal microbiota. For that, six (n=6) healthy Holstein cows were synchronized using CIDR® implants for a period of nine days. Vaginal swabs were collected on day zero (d0) and (d9) to investigate the changes in the vaginal microbiota. DNA was extracted and 16S rRNA sequences were sequenced using SE-Libraries for fragments of 300bp with minimum of 10, 000 reads per sample using MiSeq-Illumina. 16S sequences were preprocessed using Seqyclean for quality control and Mothur for data processing and classification based on Silva Database. Comparison among the type and quantity of the bacteria on d0 and d9 of the protocol were conducted using White's non-parametric t-test in STAMP, significance was considered if PTyzzerella, Clostridium, Coriobacteriaceae, Aerococcus, Acholeplasma, Macrococcus, Thiopseudomonas, Family XIII AD3011, Howardella, Elusimicrobium, Leuconostoc, Acetobacter, Mogibacteriu, Porphyromonas, Lachnospiraceae, Christensenellaceae and Dietzia ) and reduced the Stenotrophomonas . Most of the identified bacteria are commonly found in the cattle gastrointestinal tract, therefore it is possible that the bacterial colonization in the vaginal microbiome has been facilitated by the implants. However it is not known if the bacterial proliferation is caused by direct contact of the CIDR® or is due to an immune suppression in the reproductive tract, caused by the high levels of progesterone.